2002
DOI: 10.1159/000051537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Dose Oral Erythromycin on Gastric Aspirates in Ventilated Neonates Less than 32 Weeks of Gestation

Abstract: In this prospective study, the 24-hour gastric aspirate volume was carefully recorded before, 24 and 48 h after administering 1.7 mg/kg/8-hourly of oral erythromycin to 16 ventilated neonates less than 32 weeks of gestation. Their median gestational age was 28.5 weeks (range 23–31 weeks), their median birthweight was 1,045 g (range 690–1,560 g) and the median day of life at which erythromycin was commenced was 9.5 days (range 4–16 days). Prior to administering erythromycin median 24-hour gastric aspirate volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…This concept explains the contradicting finding in different trials on the use of erythromycin in premature infants. 10,19 In summary, low-dose oral erythromycin had beneficial effects on feeding intolerance and it shortened the duration of PN in preterm infants older than 32 weeks gestation. A similar effect was not found in younger preterm infants.…”
Section: Discussionmentioning
confidence: 97%
“…This concept explains the contradicting finding in different trials on the use of erythromycin in premature infants. 10,19 In summary, low-dose oral erythromycin had beneficial effects on feeding intolerance and it shortened the duration of PN in preterm infants older than 32 weeks gestation. A similar effect was not found in younger preterm infants.…”
Section: Discussionmentioning
confidence: 97%
“…8,10,11,16 -21 The results are inconsistent and contradictory, making comparison with our findings difficult. The discrepancies are due to many factors, particularly the Placebo (n ‫؍‬ 23), median (IQR) P Time to full feeding (days) 7 (6,9) 13 (9,15) Ͻ0.001* Numbers of withheld feeds or gastric residuals Ͼ 50% 1 (0, 2) 9 (2, 13) Ͻ0.001* Duration of parenteral nutrition (days) 13 (11,15) 17 (13,25) 0.03* Day to regain birth weight (days) 11 (10,14) 12 (11,15) A recent systematic review conducted in 2005 found a total of 7 studies eligible for analysis. 12 Two of the 3 randomized controlled trials involving the prophylactic approach using an antimicrobial dose (45 mg/kg/day given intravenously in 1 study 13 and 48 mg/kg/day given enterally in the other study 14 ) showed no beneficial effect on feeding in preterm infants; however, the third study 15 using low-dose EM (10 mg/kg/day given orally) found EM to be useful.…”
Section: Discussionmentioning
confidence: 99%
“…19 Eritromisin dosis rendah dapat menurunkan volume residu lambung dan memperpendek waktu transit usus pada bayi prematur, sehingga waktu pencapaian pemberian nutrisi enteral penuh (full feed) lebih cepat. 20,21 Kami tidak mendapatkan perbedaan episode terjadinya residu pada kelompok eritromisin dan plasebo. Hasil tersebut serupa dengan uji klinis acak tersamar ganda yang dilakukan oleh ElHennawy dkk 22 di Texas yang melibatkan 26 bayi prematur dengan UG 29-36 minggu.…”
Section: Pembahasanunclassified